The Ownership Structure in Building Financial Performance using Leverage as A Mediation Variable: Focusing on Manufacturing Companies That Adhere to Sharia Law - Nurshalihah, Aini Umi; Imronudin, I; Sholahuddin, Muhammad; Wiyadi, W; Haryanto, Sigit (Universitas Muhammadiyah Surakarta, 2023)
Important key factors for a company's financial decisions are leverage and ownership structure. A company can be owned by foreign owners, managerial, and institutional. This study aims to look at the effect of foreign ownership, managerial and institutional on company leverage. This study uses secondary data obtained from sharia-based manufacturing companies, namely financial reports for a period of 5 years (2016-2021). Data includes foreign ownership, managerial, institutional, leverage, and financial performance. SPSS version 20 was used to analyze the data. Regression techniques are used in evaluating the correlation between the selected variables. The analysis also involves figuring out the various correlation coefficients in the model to establish connections. The results of the study are as follows: foreign ownership has a significant positive effect on leverage, managerial ownership has no significant effect on leverage, foreign ownership has a significant positive effect on leverage, leverage has a significant negative effect on financial performance, leverage mediates significantly between foreign ownership variables on financial performance, leverage does not mediate significantly between managerial ownership variables on financial performance, and Leverage mediates significantly between institutional ownership variables on financial performance. The conclusion of this study is that foreign ownership has more influence on leverage when compared to managerial ownership. Leverage mediates foreign and institutional ownership significantly to financial performance.